Prekmurski členki v Pleteršnikovem slovarju - Agrež, Maruška (Slavia Centralis, 2015)
This paper discusses Prekmurian particles in Pleteršnik's dictionary and other relevant word inventories and selected texts written in the Prekmurian standard language. The particle, typical of the Prekmurian language is ešče. Some particles are specific to Eastern Slovene while others also occur in Kajkavian. Prekmurian particles differ from Central and Standard Slovene particles in a lexical, phonological, and derivational sense. Many Prekmurian particles are etimologically similar to their Proto-Slavic variants.
Keywords: členek; kajkavščina; leksikografija; lexicography; Prekmurian; prekmurski knjižni jezik; prekmurščina; slovarji; Slovene; slovenščina